Discontinuing amiodarone treatment prior to heart transplantation lowers incidence of severe primary graft dysfunction. Issue 2 (29th January 2020) - Hoemann, Benjamin; Takayama, Hiroo; Jennings, Douglas L.; Han, Jiho; Ando, Masahiko; Restaino, Susan; Colombo, Paolo; Farr, Maryjane; Naka, Yoshifumi; Takeda, Koji
Abstract: Background: Recent studies have shown an increased incidence of primary graft dysfunction (PGD) in patients treated with amiodarone prior to orthotopic heart transplant (OHT). We hypothesized that discontinuation of amiodarone before OHT may lower the incidence of severe PGD. Methods: This was a single‐center retrospective study of 381 adult OHT recipients between January 2010 and June 2017. Within 6 months prior to OHT, 197 did not receive amiodarone (Group 1), 142 continued amiodarone to OHT (Group 2), and 42 had amiodarone treatment discontinued before OHT (Group 3). Results: 53 (13.9%) participants developed severe PGD, 13 (6.6%) of which were in Group 1, 36 (25.4%) were in Group 2, and 4 (9.5%) were in Group 3 ( P < .001). Multivariable analysis revealed continued amiodarone treatment to OHT (Group 2; OR, 3.70; 95% CI, 1.26‐10.88; P = .018) to be an independent risk factor for the development of severe PGD when Group 1 served as the reference group. Moreover, patients in Group 3 had no difference in the risk of severe PGD (OR = 0.416, 95% CI = 0.08‐2.15; P = .296). Conclusion: We found that discontinuing amiodarone treatment prior to OHT resulted a lower incidence of severe PGD.